The Influence of Financial Literacy and Financial Technology Payment on Udayana University Management Students' Interest in Transactions - Liu, Emeralda Mitsy; Sudirman, I Made Surya Negara (The Journal of Financial, Accounting, and Economics, 2024)
This research aims to determine the influence of financial literacy and the use of Financial Technology (Fintech) Payment on the transaction interest of Management students at Udayana University. This study was conducted to understand the level of students' understanding of finance and the extent of the influence of Fintech Payments in shaping their transaction interest. The survey method was used to collect data from 94 respondents who were students of the Management Study Program at Udayana University. Data analysis used statistical techniques, including multiple regression and descriptive analysis. This study shows that financial literacy and financial payment technology have a positive impact on students' interest in making transactions. It is hoped that the results of this research will provide further insight into the relationship between financial literacy, the use of Fintech Payments, and the transaction interest of Management students, which can be the basis for developing financial literacy programs and increasing acceptance of Fintech Payments among students.